Penggunaan Automated Phase Picking pada Estimasi Hiposenter Gempa Lokal: Studi Kasus Lengan Atas Sulawesi - Huda, A.M. Miftahul; Sahara, Ain; Widyaningrum, Yekti (Jurusan Fisika, Universitas Bangka Belitung, 2021)
Hypocenter estimation was carried out in several local earthquake events in the upper arm of Sulawesi Island. The process is carried out by utilizing P and S wave arrival time data obtained through automated phase picking. The Wadati diagram was used to test the feasibility of the data and HYPOINVERSE was used to estimate the hypocenter. Vp/Vs ratio shows varied results and RMS shows poor data picking. These results have an impact on RMS values which are quite high in the estimation of the hypocenter. There was an inverse comparison of the results when viewed through the RMS value between Wadati and HYPOINVERSE. Picking data improvements need to be done in order to get a better estimate.